Kinerja Pelayanan di Puskesmas Biau Kabupaten Buol - Mutmainah Amran; Asna Aneta; Yanti Aneta (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine and describe the performance of services at the Biau Community Health Center in Buol Regency using five main indicators, namely work quality, initiative, ability, communication, and timeliness. This study uses a qualitative research approach with a descriptive method. Data were obtained through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the performance of health services at the Biau Community Health Center in Buol Regency has generally been good, but there are still several aspects that need to be improved. In terms of work quality, health workers showed commitment to providing accurate and quality services. The initiative aspect showed the ability to adapt in emergency situations, although there is still room for improvement in terms of service innovation. The ability of health workers to carry out their duties was considered adequate, with fairly good time management support. Communication between health workers and patients as well as between staff has been effective, although there is still room for improvement in terms of providing more comprehensive information. The timeliness of services is generally in accordance with established standard operating procedures.